Meningkatkan Peminat serta Pengguna Pukomtilam Dengan Menggunakan Digmat - Steven Tan; Visan Visan (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2019)
Soil fertility is not only obtained from the fertility of the land or periodic watering, but there is also away. This is also done for the fertility of plants planted in the land. One way is to apply fertilizer to the soil. The fertilizer that will be discussed is compost from Tiban Lama. This compost is processed from organic community waste and animal dung which are collected into one and processed in a shelter (TPS 3R). The processing process is carried out for one month after being ground into small pieces (small like a dust size) and watered with liquid fertilizer. After being left for a month, the garbage will be filtered to be separated from other rubbish that sticks. Finally, the fertilizer will be packed in 5kg packages. For marketing, it is still in the stage of a friend to friend. However, in student assistance, it will be assisted in marketing through social media, websites, and Instagram. On the website, it contains information about compost fertilizer. As for Instagram, it is more about fertilizer promotion. The final goal to be achieved is with this marketing, sales will grow rapidly and economic progress in Tiban Lama itself.